Karonda is a multipurpose plant for more return - Kashyap, Poonam; Kansal, Avinash; Prusty, Ashisa Kumar; Singh, S P (Indian Horticulture, 2015)
Karonda is a fruit plant which can be grown easily without much efforts in an integrated farming system.